2022
DOI: 10.26417/306bab21
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Implementation of Composite Materials in Maritime Industry on CO2 Emission’s Reduction

Abstract: The future of the composites market looks attractive with opportunities in the transportation, construction, wind energy, pipe - tank, marine, consumer goods, electrical and electronics, aerospace, and others. The composite materials market is expected to reach an estimated $40.2 billion by 2024 and it is forecast to grow at a CAGR of 3.3% from 2019 to 2024. The composite materials that have started to be used in the production of tourist boats, especially those of the yacht type, have proved in practice the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The potential of using composite materials in naval structures has drawn the attention of maritime industries in the past decades (Mouritz et al, 2001;Cao and Grenestedt, 2003). Using composite materials in naval structures can offer several advantages such as corrosion resistance, weight savings, lower CO2 emissions and energy savings (Mieloszyk, Majewska and Ostachowicz, 2021;Mirela, 2021). It has been reported that the use of composites can reduce the ship weight by 25 to 50 % from substituted elements (Hulin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The potential of using composite materials in naval structures has drawn the attention of maritime industries in the past decades (Mouritz et al, 2001;Cao and Grenestedt, 2003). Using composite materials in naval structures can offer several advantages such as corrosion resistance, weight savings, lower CO2 emissions and energy savings (Mieloszyk, Majewska and Ostachowicz, 2021;Mirela, 2021). It has been reported that the use of composites can reduce the ship weight by 25 to 50 % from substituted elements (Hulin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%